Investigation of the separation of combed heap of winter wheat - Lezhenkin, Oleksandr; Леженкін, Олександр Миколайович; Леженкин, Александр Николаевич; Halko, Serhii; Галько, Сергій Віталійович; Галько, Сергей Витальевич; Verchkov, Oleksandr; Вершков, Олександр Олександрович; Вершков, Александр Александрович; Lezhenkin, Ivan; Леженкін, Іван Олександрович; Леженкин, Иван Александрович; et al. (My University, 2021)
The article deals with the problem of separation of combed heap of winter wheat with an experimental working unit consisting of a segregator and a sieve. In order to expand the range of information on the qualitative side of the functioning of the working unit, it is suggested to introduce an additional assessment parameter – the impurity separation efficiency coefficient. Experimental studies of the technological process of the working unit were carried out using the mathematical theory of experimental design, where the response function was represented by the functional dependence of the change in the impurity separation efficiency coefficient on the specific feed of the combed heap, the oscillation frequency of the working unit and the diameter of the sieve openings. To conduct the experimental studies, the Box- Behnken design was selected. Verification of the significance of the obtained coefficients according to Student’s t-test showed that all the coefficients were significant. The adequacy of the model was assessed according to Fisher’s test. As a result of the calculations, it was established that the model was adequate and could be used for further research.
Keywords: winter wheat